Correlates of spontaneous clearance of hepatitis C virus among people with hemophilia - Zhang, Mingdong; Rosenberg, Philip S.; Brown, Deborah L.; Preiss, Liliana; Konkle, Barbara A.; Eyster, M. Elaine; Goedert, James J. (Blood, 2006)
People with hemophilia were formerly at very high risk of infection with hepatitis C virus (HCV). Approximately 20% of HCV-infected patients spontaneously clear the virus. To identify correlates of spontaneous clearance of HCV, we studied a cohort of HCV-infected hemophilic subjects without human immunodeficiency virus infection who had never been treated with interferon. Plasma HCV RNA was persistently undetectable in 192 (27.0%) of 712 HCV-seropositive subjects. In multivariate analyses, HCV clearance was more likely in subjects infected with HCV at younger age, especially with infection before age 2 years (40.1%) compared with after age 15 years (14.9%, Ptrend < .0001), and with relatively recent infection, especially after 1983 (42.8%) compared with before 1969 (18.2%, Ptrend < .0001). HCV clearance was marginally reduced with African ancestry (19%) and greatly increased with chronic hepatitis B virus (HBV) infection (59.1%, P = .001). Resolved HBV infection, coagulopathy types and severity, types of clotting factor treatment, and sex were not associated with HCV clearance. In conclusion, hemophilic subjects coinfected with chronic HBV and those infected with HCV before age 2 years or after 1983 were significantly more likely to spontaneously clear HCV viremia. These data highlight and clarify the importance of nongenetic determinants in spontaneous recovery from HCV infection.